Consumer response to return policies of selected local brand retailers of women's apparel - Briones, Erika Elaine C.; Orendain, Iskra Gabrielle R. (2004.)
This study on return policies of selected local brand retailers of women's apparel is based on the fundamentals of Total Quality Management - to create a customer-focused culture with customer-oriented systems. With nine selected local brand retailers of women's apparel, this study aims to discover if Philippine retailers respect the rights of consumers by having clear and fair return policies. One hundred customers of these retailers were surveyed to find out further if Filipinos practice their rights as consumers by being aware of such legalities such as the return policy. Great quantities of research and studies have been made on consumers - their profiles, attitudes, behaviors, reactions, and demands among many other subjects. Specifically, this study is based on customer complaints and how organizations should deal with this negative feedback and use them for the improvement of the organization. One way is to promote customer-friendly policies for customer complaints that organizations can use to improve their products, service, style and other systems. The study used a methodology based on descriptive research and both qualitative and quantitative approaches were used to gather information from the nine retailers and the one hundred customers. The return policies of the retailers were collected and the customers were asked about their shopping behaviors and their attitudes towards return policies, what they want in return policy, and how good and bad return policy affects them. The findings of the research show that respondents clearly want a more reasonable policy other than what is being implemented by the retailers now. A lot of improvement is needed by the retailers in the Philippines until they achieve Total Quality Management.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Stores, Retail -- Philippines -- Return policy